Vern : custodian of the universe - Waiters, Tyrell (Nobrow Ltd, 2023)
"On the edge of burnout, Vern decides to return to his family in the Sunshine State to start over. Starting a new dead-end job as a custodian at Quasar -- a local science facility with a shady motive -- he shrugs on his uniform, grabs a mop and bucket, and trudges off to clean up... Black holes? Space-time anomalies? Galactic ooze? Things aren't entirely what they seem at Quasar, and when Vern accidentally plugs in a mysterious machine and finds himself standing on the brink of the destruction of every planet in the Multiverse, he's presented with the greatest question of all: what is the point? Fans of Ben Passmore's personal and political comics -- as well as classic sci-fi comedies like Bill & Ted's Excellent Adventure and Rick and Morty -- will enjoy this world of hyper fantasy with a touch of humor, as told by a Black creator." --